Social inequality in tooth extraction in a Brazilian insured working population - Neto JMS, Nadanovsky P. (Blackwell Synergy, 2007)
Given the scant evidence of the socioeconomic gradient in tooth loss incidence, the purpose of this study was to compare the odds of individuals of distinct social strata being subjected to tooth extraction.